2018
DOI: 10.3892/etm.2018.7099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paraquat on IL‑6 and TNF‑α in macrophages

Abstract: Effects of paraquat (PQ) on interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in macrophages were investigated. Different concentrations of PQ were added to mouse macrophage RAW264.7 for culture. According to different concentrations of PQ, mice were divided into micro concentration (0.01 mmol/l), low concentration (0.1 mmol/l), medium concentration (1 mmol/l), high concentration (10 mmol/l), and control groups without PQ. Trypan blue solution was used for detecting cell viability, a microplate reader f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…LPS and paraquat treatment have previously been shown to induce microglial activation in the SNc [67], and we presently observed that DSS pre-treatment enhanced this activation. Despite this, SNc dopaminergic neuronal loss was not influenced by either DSS or VSL#3, which is surprising given the evidence linking microglial state to neurodegeneration [65,[68][69][70]. Yet, we found that LPS plus paraquat also induced increase in astroglia marker (at least a subset of astrocytes, as determined by GFAP) and this was unaffected by the DSS treatments.…”
Section: Discussioncontrasting
confidence: 72%
“…LPS and paraquat treatment have previously been shown to induce microglial activation in the SNc [67], and we presently observed that DSS pre-treatment enhanced this activation. Despite this, SNc dopaminergic neuronal loss was not influenced by either DSS or VSL#3, which is surprising given the evidence linking microglial state to neurodegeneration [65,[68][69][70]. Yet, we found that LPS plus paraquat also induced increase in astroglia marker (at least a subset of astrocytes, as determined by GFAP) and this was unaffected by the DSS treatments.…”
Section: Discussioncontrasting
confidence: 72%
“…Importantly, we did find that paraquat induce increases in lung (and heart) weight, which could reflect pathology owing to cellular derangement or infiltration, as was previously reported with paraquat poisoning [245,246]. Further, direct application of paraquat onto cultured RAW264.7 macrophages induced an elevation of IL-6 that accompanied the release of reactive oxidative species [247]. The NF-kB rise within the striatum after 1 month is interesting in that this is a primary inflammatory transcription factor that regulates IL-1b and TNF-a signaling.…”
Section: Figure 27supporting
confidence: 78%
“…Interestingly DSS pre-treatment significantly enhanced this activation while VSL#3 treatment trended to prevent this. Despite this, TH+ cell loss was not impacted by these microglial alterations which is surprising given the literature thus far examining the role of microglia in paraquat models of PD [150,153,247,316]. Given the increase we observed in GFAP expression following LPS and paraquat treatment, our TH+ cell loss may additionally be due to alteration in astrocyte function that may not be influenced by VSL#3 or DSS treatment.…”
Section: Dss Treatment Increased Intestinal Tnf-α and Il-1β Mrna Exprmentioning
confidence: 49%
“…The mechanism of acute paraquat poisoning is complex, with many inflammatory factors and cytokines involved (30). Acute paraquat poisoning can lead to a strong inflammatory reaction (31). Previous studies reported that IL-10 mRNA expression level was increased in paraquat poisoned rats, IL-10 level was decreased by sucralfate treatment and the lung and kidney injuries of the rats were also improved (13,14).…”
Section: Discussionmentioning
confidence: 99%